Consumer Insight-Based Social Media Marketing Strategy To Increase Brand Awareness: A Case Study Of Jumpa Asa Coffee Shop - Nahdah Izzatisilmi; Syifa Ayu Aulia (International Journal of Management and Business Economics, 2026)
Brand awareness had become one of the key challenges for local coffee shops operating in highly competitive markets. Jumpa Asa Coffee Shop experienced relatively low brand recognition despite offering a distinctive brand concept and quality products. This study aimed to develop and implement a consumer and market insight-based social media marketing strategy through content and campaign deliverables to improve brand awareness. This project employed interviews, observations, questionnaires (n=165 respondents for main survey, n=41 for pre-survey, n=45 for post-survey), competitor analysis, and social media analytics to identify consumer behavior, market characteristics, and audience preferences. The findings informed a structured content strategy and digital campaign on Instagram over a 4-week period (18 May – 15 June 2026), during which 20 content posts were published (13 Reels, 5 Feeds, and 2 Stories), including a campaign challenge that attracted 12 participants. The implementation demonstrated significant improvements in digital marketing performance, including reach increasing from 924 to 6,064 accounts (555.6% increase), impressions rising from 25,495 to 41,455 (62.6% increase), profile visits growing from 1,306 to 2,387 (82.8% increase), engagement rate jumping from 3.63% to 12.2% (236% increase), and followers increasing from 422 to 446 (5.7% increase). The results indicated that integrating consumer and market insights into content planning enabled more relevant communication with target audiences and strengthened brand awareness among local consumers. This study contributed practical evidence that consumer insight-based social media marketing could serve as an effective branding strategy for small and medium-sized coffee shop businesses operating in competitive environments.